Detection of viable but non-culturable legionella in hospital water network following monochloramine disinfection. Issue 1 (January 2018) - Casini, B.; Baggiani, A.; Totaro, M.; Mansi, A.; Costa, A.L.; Aquino, F.; Miccoli, M.; Valentini, P.; Bruschi, F.; Lopalco, P.L.; Privitera, G.
Summary: Background: Prevention of legionellosis remains a critical issue in healthcare settings where monochloramine (MC) disinfection was recently introduced as an alternative to chlorine dioxide in controlling Legionella spp. contamination of the hospital water network. Continuous treatments with low MC doses in some instances have induced a viable but non-culturable state (VBNC) of Legionella spp. Aim: To investigate the occurrence of such dormant cells during a long period of continuous MC treatment. Methods: Between November 2010 and April 2015, 162 water and biofilm samples were collected and Legionella spp. isolated in accordance with standard procedures. In sampling sites where MC was <1.5 mg/L, VBNC cells were investigated by ethidium monoazide bromide (EMA)–real-time polymerase chain reaction (qPCR) and 'resuscitation' test into Acanthamoeba polyphaga CCAP 1501/18. According to the Health Protection Agency protocol, free-living protozoa were researched in 60 five-litre water samples. Findings: In all, 136 out of 156 (87.2%) of the samples taken from sites previously positive for L. pneumophila ST269 were negative by culture, but only 47 (34.5%) negative by qPCR. Although no positive results were obtained by EMA-qPCR, four out of 22 samples associated with MC concentration of 1.3 ± 0.5 mg/L showed VBNC legionella resuscitation. The presence of the amoeba A. polyphaga in the hospital water network was demonstrated. Conclusion: Our study is the first report evidencing the emergence of VNBC legionella during a long period of continuous MC treatment of a hospital water network, highlighting the importance of keeping an appropriate and uninterrupted MC dosage to ensure the control of legionella colonization in hospital water supplies.